NiCr15Fe alloy surface high-temperature anti-oxidation coating material and preparation method thereof

By using high-speed laser cladding technology of NiCr15Fe alloy and CoCrNi alloy powder on the surface of nickel alloy, a high-temperature anti-oxidation coating is formed, which solves the corrosion and wear problems of nickel alloy under high temperature and extreme chemical conditions, and achieves high hardness and corrosion resistance , suitable for the repair of critical components.

CN119177440APending Publication Date: 2024-12-24GUANGDONG SONGSHAN POLYTECHNIC COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411249326.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The prior art is difficult to form an efficient antioxidant coating on the surface of nickel alloys under high temperature conditions, especially in the problem of corrosion and wear under extreme chemical conditions.

Method used

Using NiCr15Fe alloy as the matrix material, high-speed laser cladding is performed through a ytterbium-doped fiber laser, combined with CoCrNi alloy powder as the cladding material, specific laser cladding process parameters, such as laser power, scanning speed and powder feeding speed, to form high temperature Antioxidant coating, the coating is divided into upper, middle, lower and transition layers, and uses a fast heat quench process to refine grains and produce unbalanced compounds to improve hardness.

Benefits of technology

Achieve high hardness of the coating (up to 321.9HV), enhances the toughness and ductility of the coating, and maintains corrosion resistance under extreme conditions, improves cladding efficiency, suitable for repairing critical zeros of susceptibility to corrosion and wear part.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177440A_ABST
    Figure CN119177440A_ABST
Patent Text Reader

Abstract

The invention provides a NiCr15Fe alloy surface high-temperature anti-oxidation coating material and a preparation method thereof, the method takes NiCr15Fe alloy as a matrix material and CoCrNi alloy powder as a cladding material, the matrix material is pretreated, and an ytterbium-doped fiber laser is adopted to clad the cladding material on the matrix material according to set laser cladding process parameters. According to the method, a cladding layer which is compact in structure and free of pore cracks can be formed, it can be seen from the structure morphology of the middle of the cladding layer that the cladding layer is jointly composed of directional columnar crystal branches, non-directional crystal branches and a small part of isometric crystals, and therefore good toughness and ductility are achieved under the condition of high strength and rigidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of laser cladding coatings, and in particular to a NiCr15Fe alloy surface high-temperature anti-oxidation coating material and a preparation method thereof. Background Art

[0002] Key components of high-end equipment are prone to failures such as wear and corrosion, causing huge losses in industrial production. In recent decades, laser cladding technology has been widely used in the repair of key components. Compared with traditional cladding, high-speed laser cladding has the advantages of high efficiency, precision, and low heat, which has attracted the attention of researchers. Studies have shown that the microstructure of the cladding layer, such as grain size, morphology, and phase distribution, has an important influence on the properties of the coating. Therefore, the microstructure of the cladding layer is regulated by the laser cladding process to obtain better coating quality and mechanical properties, and to ensure the reliability and durability of the cladding layer in specific application scenarios.

[0003] Nickel alloys have excellent corrosion resistance, high temperature strength and good mechanical properties, so they are widely used in the oil and gas industry, aerospace industry, electronics and electrical industry, etc. NiCoCr has excellent corrosion resistance, high temperature strength, cladding performance, mechanical properties, plasticity and processing properties, which makes it an ideal cladding material for nickel alloy surfaces.

[0004] Laser clad NiCoCr alloys usually have a small and uniform grain size, which helps to improve the hardness and toughness of the coating. In addition, laser cladding can lead to slightly different grain orientations compared to the substrate, which can change the mechanical properties of the coating. Studies have found that the distribution of alloying elements changes during laser cladding, forming complex phase regions. By controlling the cladding parameters, the distribution and phase ratio of alloying elements can be adjusted to achieve specific mechanical property requirements, such as hardness, strength, and wear resistance. During the laser cladding process, some elements in the alloy may undergo solid solution, dissolution, or phase transformation. These phase changes and phase precipitation can affect the mechanical properties of the coating, such as strength, toughness, and deformation ability. Laser clad NiCoCr alloy coatings usually have high hardness and good wear resistance. Relatively small grain size and uniform distribution of alloying elements can provide significant hardness increase and wear resistance. Summary of the invention

[0005] In view of the above situation, the main purpose of the present invention is to propose a NiCr15Fe alloy surface high temperature anti-oxidation coating material and a preparation method to solve the above technical problems.

[0006] The present invention proposes a method for preparing a high-temperature anti-oxidation coating material on the surface of a NiCr15Fe alloy, the method comprising the following steps:

[0007] NiCr15Fe alloy is used as the base material, CoCrNi alloy powder is used as the cladding material, the base material is pretreated, and the cladding material is clad on the base material using an ytterbium-doped fiber laser according to the set laser cladding process parameters;

[0008] The set laser cladding process parameters are: laser power 1300-2100 / W, scanning speed 40-120 mm / s, powder feeding speed 2 r / min, and spot diameter 2 / mm.

[0009] Furthermore, the laser cladding process parameters were set as follows: laser power 1900 / W, scanning speed 100 mm / s, powder feeding speed 2 r / min, and spot diameter 2 / mm.

[0010] Furthermore, during the cladding process, the cladding material is blown out using nitrogen.

[0011] Furthermore, the NiCr15Fe alloy composition includes, by mass percentage, 72.50% Ni, 14.10% Cr, 9.80% Fe, 0.30% Mn, 0.30% Ti, 0.35% Al, 0.10% C, 0.50% Si and 2.05% inevitable impurities.

[0012] Furthermore, the CoCrNi alloy powder comprises, by mass percentage, 34.54% Ni, 34.47% Co, 30.55% Cr and 0.44% inevitable impurities.

[0013] Furthermore, the base material is pretreated by sanding to remove the surface oxide layer, cleaning to remove oil and dirt with ethanol, and drying.

[0014] Furthermore, the geometric dimensions of the cladding layer are as follows: the molten pool width is 480.8-1456.8 μm, the total depth is 143.7-491.3 μm, the molten pool depth is 69.5-373.5 μm, and the layer height is 24.2-75.1 μm.

[0015] The present invention also provides a NiCr15Fe alloy surface high temperature anti-oxidation coating material, and the coating material is prepared by the above-mentioned method for preparing the NiCr15Fe alloy surface high temperature anti-oxidation coating material.

[0016] Further, the cross section of the coating material includes an upper layer, a middle layer, a lower layer and a transition layer at the junction with the substrate, and the composition of the upper layer of the coating material includes 27.28% Cr, 31.91% Fe, 19.32% Co and 21.49% Ni in terms of atomic percentage;

[0017] The composition of the middle layer of the coating material includes 26.44% Cr, 37.94% Fe, 16.11% Co and 19.51% Ni in terms of atomic percentage;

[0018] The composition of the lower layer of the coating material includes 21.11% Cr, 71.69% Fe, 0.1% Co and 7.1% Ni in atomic percentage.

[0019] Furthermore, the upper layer of the coating material is a fine crystal region, the middle layer of the coating material is a mixed region of equiaxed crystals and columnar crystals, the lower layer of the coating material is a columnar crystal region, and a σ phase is generated in the transition layer at the junction of the coating material and the substrate.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. Rapid heating and rapid cooling during the cladding process effectively refines the coating grains, and fine grain strengthening provides favorable conditions for improving the coating hardness; secondly, during the rapid heating and rapid cooling process, non-equilibrium compounds are easily generated in the coating, part of which provides conditions for solid solution strengthening, and part of the non-equilibrium compounds are hard phases, which further improves the coating hardness. The hardness of the coating material prepared by the present invention can reach up to 321.9HV, far exceeding the hardness of the substrate material.

[0022] 2. The present invention can form a cladding layer with dense structure and no pores or cracks. From the structure morphology of the middle part of the cladding layer, it can be seen that it is composed of directional columnar crystal dendrites, non-directional crystal dendrites and a small part of equiaxed crystals. Therefore, it has good toughness and ductility under the condition of high strength and stiffness.

[0023] 3. The base material and cladding material used in the present invention are both corrosion-resistant materials. No protective gas is required during the cladding process, and no post-processing is required after the cladding is completed, so they can be directly put into use, which can greatly improve the cladding efficiency.

[0024] 4. The present invention adopts high-speed laser cladding technology, which has the advantages of high efficiency and energy saving compared with the existing technology. At the same time, the substrate is a corrosion-resistant material, but this material is easily corroded under extreme chemical conditions. This technology is applied to the repair of the stirring shaft of high-end imported chemical equipment in a chemical plant in Jiangxi Province. The coating prepared by it is mainly used for the repair process of key components that are prone to corrosion and wear. After the repair is completed, it can be put into use.

[0025] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description or learned through embodiments of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The powder electron microscope image of the alloy powder morphology provided on the market;

[0027] Figure 2 A comparison diagram of the appearance of single-pass laser cladding prepared in Examples 1 to 9;

[0028] Figure 3 This is a comparison diagram of the cladding layer size and dilution rate at different laser powers in Examples 1 to 5;

[0029] Figure 4 This is a comparison diagram of the cladding layer size and dilution rate at different scanning speeds in Examples 6 to 9;

[0030] Figure 5 3 are the coating morphology images of Example 5 and Example 9;

[0031] Figure 6 The cross-sectional microscopic morphology of the cladding layer prepared for Example 4;

[0032] Figure 7 The microstructure and composition diagram of the cladding layer prepared for Example 4;

[0033] Figure 8 This is a comparison chart of the hardness of the cladding layers prepared in Examples 1 to 9 and the base material. DETAILED DESCRIPTION

[0034] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0035] These and other aspects of the embodiments of the present invention will be apparent with reference to the following description and accompanying drawings. In these descriptions and accompanying drawings, some specific implementations of the embodiments of the present invention are specifically disclosed to represent some ways of implementing the principles of the embodiments of the present invention, but it should be understood that the scope of the embodiments of the present invention is not limited thereto.

[0036] Example 1

[0037] A method for preparing a high-temperature anti-oxidation coating material on the surface of a NiCr15Fe alloy, the method comprising the following steps:

[0038] NiCr15Fe alloy is used as a base material, and the base material is sanded to remove the surface oxide layer, cleaned with ethanol to remove oil and dirt, and dried. The composition of the NiCr15Fe alloy includes, by mass percentage, 72.50% Ni, 14.10% Cr, 9.80% Fe, 0.30% Mn, 0.30% Ti, 0.35% Al, 0.10% C, 0.50% Si and 2.05% inevitable impurities.

[0039] CoCrNi alloy powder is used as the cladding material, wherein the CoCrNi alloy powder comprises, by mass percentage, 34.54% Ni, 34.47% Co, 30.55% Cr, and 0.44% inevitable impurities.

[0040] The set laser cladding process parameters are: laser power 1300 / W, scanning speed 40mm / s, powder feeding speed 2r / min, and spot diameter 2 / mm.

[0041] An ytterbium-doped fiber laser is used according to the set laser cladding process parameters to blow out the cladding material and clad it on the base material through nitrogen blowing to obtain a high-temperature anti-oxidation coating material, which is recorded as S1.

[0042] Example 2

[0043] A method for preparing a high-temperature anti-oxidation coating material on the surface of a NiCr15Fe alloy, the method comprising the following steps:

[0044] NiCr15Fe alloy is used as a base material, and the base material is sanded to remove the surface oxide layer, cleaned with ethanol to remove oil and dirt, and dried. The composition of the NiCr15Fe alloy includes, by mass percentage, 72.50% Ni, 14.10% Cr, 9.80% Fe, 0.30% Mn, 0.30% Ti, 0.35% Al, 0.10% C, 0.50% Si and 2.05% inevitable impurities.

[0045] CoCrNi alloy powder is used as the cladding material, wherein the CoCrNi alloy powder comprises, by mass percentage, 34.54% Ni, 34.47% Co, 30.55% Cr and 0.44% inevitable impurities.

[0046] The set laser cladding process parameters are: laser power 1500 / W, scanning speed 40mm / s, powder feeding speed 2r / min, and spot diameter 2 / mm.

[0047] An ytterbium-doped fiber laser is used according to the set laser cladding process parameters to blow out the cladding material and clad it on the base material through nitrogen blowing to obtain a high-temperature anti-oxidation coating material, which is recorded as S2.

[0048] Example 3

[0049] A method for preparing a high-temperature anti-oxidation coating material on the surface of a NiCr15Fe alloy, the method comprising the following steps:

[0050] NiCr15Fe alloy is used as a base material, and the base material is sanded to remove the surface oxide layer, cleaned with ethanol to remove oil and dirt, and dried. The composition of the NiCr15Fe alloy includes, by mass percentage, 72.50% Ni, 14.10% Cr, 9.80% Fe, 0.30% Mn, 0.30% Ti, 0.35% Al, 0.10% C, 0.50% Si and 2.05% inevitable impurities.

[0051] CoCrNi alloy powder is used as the cladding material, wherein the CoCrNi alloy powder comprises, by mass percentage, 34.54% Ni, 34.47% Co, 30.55% Cr and 0.44% inevitable impurities.

[0052] The set laser cladding process parameters are: laser power 1700 / W, scanning speed 40mm / s, powder feeding speed 2r / min, and spot diameter 2 / mm.

[0053] An ytterbium-doped fiber laser is used according to the set laser cladding process parameters to blow out the cladding material and clad it on the base material through nitrogen blowing to obtain a high-temperature anti-oxidation coating material, which is recorded as S3.

[0054] Example 4

[0055] A method for preparing a high-temperature anti-oxidation coating material on the surface of a NiCr15Fe alloy, the method comprising the following steps:

[0056] NiCr15Fe alloy is used as a base material, and the base material is sanded to remove the surface oxide layer, cleaned with ethanol to remove oil and dirt, and dried. The composition of the NiCr15Fe alloy includes, by mass percentage, 72.50% Ni, 14.10% Cr, 9.80% Fe, 0.30% Mn, 0.30% Ti, 0.35% Al, 0.10% C, 0.50% Si and 2.05% inevitable impurities.

[0057] CoCrNi alloy powder is used as the cladding material, wherein the CoCrNi alloy powder comprises, by mass percentage, 34.54% Ni, 34.47% Co, 30.55% Cr and 0.44% inevitable impurities.

[0058] The set laser cladding process parameters are: laser power 1900 / W, scanning speed 40mm / s, powder feeding speed 2r / min, and spot diameter 2 / mm.

[0059] An ytterbium-doped fiber laser is used according to the set laser cladding process parameters to blow out the cladding material and clad it on the base material through nitrogen blowing to obtain a high-temperature anti-oxidation coating material, which is recorded as S5.

[0060] Example 5

[0061] A method for preparing a high-temperature anti-oxidation coating material on the surface of a NiCr15Fe alloy, the method comprising the following steps:

[0062] NiCr15Fe alloy is used as a base material, and the base material is sanded to remove the surface oxide layer, cleaned with ethanol to remove oil and dirt, and dried. The composition of the NiCr15Fe alloy includes, by mass percentage, 72.50% Ni, 14.10% Cr, 9.80% Fe, 0.30% Mn, 0.30% Ti, 0.35% A1, 0.10% C, 0.50% Si and 2.05% inevitable impurities.

[0063] CoCrNi alloy powder is used as the cladding material, wherein the CoCrNi alloy powder comprises, by mass percentage, 34.54% Ni, 34.47% Co, 30.55% Cr and 0.44% inevitable impurities.

[0064] The set laser cladding process parameters are: laser power 2100 / W, scanning speed 40mm / s, powder feeding speed 2r / min, and spot diameter 2 / mm.

[0065] An ytterbium-doped fiber laser is used according to the set laser cladding process parameters to blow out the cladding material and clad it on the base material through nitrogen blowing to obtain a high-temperature anti-oxidation coating material, which is recorded as S5.

[0066] Example 6

[0067] A method for preparing a high-temperature anti-oxidation coating material on the surface of a NiCr15Fe alloy, the method comprising the following steps:

[0068] NiCr15Fe alloy is used as a base material, and the base material is sanded to remove the surface oxide layer, cleaned with ethanol to remove oil and dirt, and dried. The composition of the NiCr15Fe alloy includes, by mass percentage, 72.50% Ni, 14.10% Cr, 9.80% Fe, 0.30% Mn, 0.30% Ti, 0.35% Al, 0.10% C, 0.50% Si and 2.05% inevitable impurities.

[0069] CoCrNi alloy powder is used as the cladding material, wherein the CoCrNi alloy powder comprises, by mass percentage, 34.54% Ni, 34.47% Co, 30.55% Cr and 0.44% inevitable impurities.

[0070] The set laser cladding process parameters are: laser power 1900 / W, scanning speed 60mm / s, powder feeding speed 2r / min, and spot diameter 2 / mm.

[0071] An ytterbium-doped fiber laser is used according to the set laser cladding process parameters to blow out the cladding material and clad it on the base material through nitrogen blowing to obtain a high-temperature anti-oxidation coating material, which is recorded as S6.

[0072] Example 7

[0073] A method for preparing a high-temperature anti-oxidation coating material on the surface of a NiCr15Fe alloy, the method comprising the following steps:

[0074] NiCr15Fe alloy is used as a base material, and the base material is sanded to remove the surface oxide layer, cleaned with ethanol to remove oil and dirt, and dried. The composition of the NiCr15Fe alloy includes, by mass percentage, 72.50% Ni, 14.10% Cr, 9.80% Fe, 0.30% Mn, 0.30% Ti, 0.35% Al, 0.10% C, 0.50% Si and 2.05% inevitable impurities.

[0075] CoCrNi alloy powder is used as the cladding material, wherein the CoCrNi alloy powder comprises, by mass percentage, 34.54% Ni, 34.47% Co, 30.55% Cr and 0.44% inevitable impurities.

[0076] The set laser cladding process parameters are: laser power 1900 / W, scanning speed 80mm / s, powder feeding speed 2r / min, and spot diameter 2 / mm.

[0077] An ytterbium-doped fiber laser is used according to the set laser cladding process parameters to blow out the cladding material and clad it on the base material through nitrogen blowing to obtain a high-temperature anti-oxidation coating material, which is recorded as S7.

[0078] Example 8

[0079] A method for preparing a high-temperature anti-oxidation coating material on the surface of a NiCr15Fe alloy, the method comprising the following steps:

[0080] NiCr15Fe alloy is used as a base material, and the base material is sanded to remove the surface oxide layer, cleaned with ethanol to remove oil and dirt, and dried. The composition of the NiCr15Fe alloy includes, by mass percentage, 72.50% Ni, 14.10% Cr, 9.80% Fe, 0.30% Mn, 0.30% Ti, 0.35% A1, 0.10% C, 0.50% Si and 2.05% inevitable impurities.

[0081] CoCrNi alloy powder is used as the cladding material, wherein the CoCrNi alloy powder comprises, by mass percentage, 34.54% Ni, 34.47% Co, 30.55% Cr and 0.44% inevitable impurities.

[0082] The set laser cladding process parameters are: laser power 1900 / W, scanning speed 100mm / s, powder feeding speed 2r / min, and spot diameter 2 / mm.

[0083] An ytterbium-doped fiber laser is used according to the set laser cladding process parameters to blow out the cladding material and clad it on the base material through nitrogen blowing to obtain a high-temperature anti-oxidation coating material, which is recorded as S8.

[0084] Example 9

[0085] A method for preparing a high-temperature anti-oxidation coating material on the surface of a NiCr15Fe alloy, the method comprising the following steps:

[0086] NiCr15Fe alloy is used as a base material, and the base material is sanded to remove the surface oxide layer, cleaned with ethanol to remove oil and dirt, and dried. The composition of the NiCr15Fe alloy includes, by mass percentage, 72.50% Ni, 14.10% Cr, 9.80% Fe, 0.30% Mn, 0.30% Ti, 0.35% Al, 0.10% C, 0.50% Si and 2.05% inevitable impurities.

[0087] CoCrNi alloy powder is used as the cladding material, wherein the CoCrNi alloy powder comprises, by mass percentage, 34.54% Ni, 34.47% Co, 30.55% Cr and 0.44% inevitable impurities.

[0088] The set laser cladding process parameters are: laser power 1900 / W, scanning speed 120mm / s, powder feeding speed 2r / min, and spot diameter 2 / mm.

[0089] An ytterbium-doped fiber laser is used according to the set laser cladding process parameters to blow out the cladding material and clad it on the base material through nitrogen blowing to obtain a high-temperature anti-oxidation coating material, which is recorded as S9.

[0090] Example 10

[0091] The present invention also provides a NiCr15Fe alloy surface high temperature anti-oxidation coating material, the coating material is prepared by the above-mentioned NiCr15Fe alloy surface high temperature anti-oxidation coating material preparation method;

[0092] The cross section of the coating material includes an upper layer, a middle layer, a lower layer and a transition layer at the junction with the substrate, and the composition of the upper layer of the coating material includes 27.28% Cr, 31.91% Fe, 19.32% Co and 21.49% Ni in terms of atomic percentage;

[0093] The composition of the middle layer of the coating material includes 26.44% Cr, 37.94% Fe, 16.11% Co and 19.51% Ni in terms of atomic percentage;

[0094] The composition of the lower layer of the coating material includes 21.11% Cr, 71.69% Fe, 0.1% Co and 7.1% Ni in atomic percentage.

[0095] In order to verify the performance of the material prepared by the present invention, experimental verification was carried out using materials and equipment available on the market.

[0096] The base material is NiCr15Fe alloy with a size of 75X50mm produced by Dongguan Huanggang Metal Materials Co., Ltd. (the composition is shown in Table 1), and the cladding material is CoCrNi alloy powder produced by Hebei Guifa Alloy Wear Resistant Materials Co., Ltd. (the composition is shown in Table 2). Figure 1 shown.

[0097] Table 1 Chemical composition of NiCr15Fe alloy (mass fraction, %)

[0098]

[0099] Table 2 Chemical composition of CoCrNi alloy powder (mass fraction, %)

[0100]

[0101] The laser cladding equipment uses a high-speed laser cladding machine from Zhongke Yuchen Laser Technology Co., Ltd., and the laser is the YLS6000 ytterbium-doped fiber laser produced by IPG.

[0102] Microscopic morphology observation was performed using a RX50M metallographic microscope produced by Ningbo Sunny Optical Instrument Co., Ltd. and a JSM-IT710HR scanning electron microscope produced by JEOL.

[0103] The hardness test was performed using a microhardness tester model MHVS-1000BZD produced by Shanghai Lidun Instrument Testing Technology Co., Ltd.

[0104] The operating steps of Examples 1 to 9 are repeated using commercially available base materials and cladding materials to obtain high-temperature anti-oxidation coating materials S1 to S9.

[0105] like Figure 2The figure shows a single-pass laser cladding experiment on the substrate surface with different laser cladding process parameters. S1-S5 are the results obtained at a scanning speed of 40mm / S and laser power ranging from 1.3KW to 2.1KW. From the surface of the cladding layer, it can be seen that with the increase of laser power, the width of the single-pass cladding layer continues to increase.

[0106] S6-S9 are cladding layers obtained when the laser power is 1.9KW and the scanning speed increases from 60mm / S to 120mm / s. The appearance color of the cladding layer changes from the original color of the metal to golden yellow, and the width of the cladding layer becomes narrower with the increase of the scanning speed. When the scanning speed continues to increase to 120mm / s, it can be seen on the S9 sample that the cladding layer is no longer continuous, and intermittent point-like metal melting points are formed on the surface of the substrate.

[0107] Based on the previous macroscopic analysis, the geometric dimensions and dilution rate of the cladding layer are analyzed next. Figure 3 Comparison of the size and dilution rate of the cladding layer obtained at different laser powers from S1 to S5. Figure 3 As shown in a, as the laser power continues to increase, the overall thickness and width of the cladding layer continue to increase. When the laser power reaches the maximum value of 2.1KW, the cladding thickness and width reach the maximum values ​​of 491.3μm and 1456.8μm respectively. The main reason is that as the laser power increases, the unit energy density increases, and the energy absorbed per unit area of ​​the cladding material and the substrate surface is large, resulting in deeper metal participating in the metallurgical reaction of the substrate; in addition, since the maximum cladding layer width in the experiment is less than the spot diameter of 2μm, the cladding layer width does not reach the edge of the spot, so the cladding layer thickness and width continue to increase with the increase of laser power. Figure 3 Figure b is a graph of the depth and height of the molten pool. As the power continues to increase, the depth of the molten pool does not change much before 1.7KW. When the laser power is greater than 1.7KW, the depth of the molten pool increases significantly. As the laser power reaches 2.1KW, the depth of the molten pool reaches a maximum value of 373.5μm. When the power is lower than 1.7KW, the height of the molten pool continues to decrease. When the power is higher than 1.7KW, the height of the molten pool varies around 70μm, close to a state of equilibrium. The main reason is that in the early stage of the increase in laser power, the heat of the molten pool becomes larger and larger, and the molten metal becomes more and more and accumulates on the surface of the cladding layer. Under relatively low laser power conditions, the height of the molten pool continues to increase. When the laser power increases to a certain value, factors such as the fluidity, wettability and surface tension of the liquid metal material prevent the height of the molten pool from increasing. Therefore, as the power increases, the height of the molten pool tends to balance when it reaches a certain value. Figure 3 As shown in Figure c, the dilution rate of the cladding layer increases with the increase of laser power, and the maximum change occurs when the power increases from 1.7KW to 1.9KW, and the dilution rate of the cladding layer increases from 62.01% to 73.00%.

[0108] Based on this, the laser power is positively correlated with the cladding layer thickness, width, molten pool depth and dilution rate, but negatively correlated with the molten pool height within a certain range, and finally tends to balance.

[0109] Figure 4 This is a comparison chart of the cladding layer size and dilution rate at different scanning speeds S6-S9. Figure 4 As shown in Figure 2, the thickness and width of the cladding layer, the depth and height of the molten pool, and the dilution rate are all negatively correlated with the scanning speed. Figure 4 Figure a shows the relationship between the thickness and width of the cladding layer and the scanning speed. Figure 4 Figure b shows the relationship between the molten pool depth, height and scanning speed. Figure 4 As shown in figure a, the cladding layer width decreases the most when the scanning speed increases from 40 mm / s to 60 mm / s, and the cladding layer width decreases from 844.4 μm to 618.3 μm. As the scanning speed continues to increase, the cladding width continues to decrease, but tends to be gentle.

[0110] As the scanning speed increases, the laser stays on the material surface for a shorter time, the cladding material and the substrate receive less laser energy and the temperature is low. Part of the material fails to reach a molten state, the alloy powder is carried away by the powder feeding gas, and the molten volume of the substrate becomes smaller. Due to the above reasons, the thickness and width of the cladding layer, the depth and height of the molten pool, and the dilution rate all decrease as the scanning speed decreases.

[0111] Table 3 Geometric dimensions of cladding layer

[0112]

[0113]

[0114] like Figure 5 The following are the coating morphologies of samples S5 and S9. Figure 5 In figure a, we can see that there are a lot of cracks running from the top of the coating to the bottom of the coating. The main reason is that the power reaches 2.1KW, the cladding material is heated greatly, and the thermal stress in the coating increases during the solidification process, causing the coating to crack. Figure 5 In figure b, circular pores can be seen in the coating. The main reason is that the scanning speed is too high, the coating solidifies quickly, and the gas or powder-carrying gas generated in the metallurgical process has no time to be discharged and solidifies in the coating. Therefore, excessive power or scanning speed will significantly affect the quality of the cladding layer, resulting in defects such as cracks or pores inside the coating.

[0115] like Figure 6 Figure a is a schematic diagram of cladding. Figure 6Figure b is the microscopic morphology of the cross section of a single laser cladding layer, in which a dense cladding layer without pores and cracks is formed. The cladding layer is divided into a molten pool and a transition layer. At the junction of the cladding layer and the substrate, i.e., the transition layer, an obvious white bright light band can be seen, indicating that a good metallurgical bond is formed between the substrate and the cladding layer. Figure 6 c / d / e are the microstructures of the upper, middle and lower cladding layers respectively. From the microstructure of the upper cladding layer, it can be seen that it is composed of non-directional fine grains. The main reason is that the upper cladding layer directly exchanges heat with the air, and the heat of the molten pool is lost quickly, resulting in a fast cooling speed, a large degree of undercooling and rapid solidification of the upper cladding layer. According to the relationship between undercooling and grain refinement, it can be seen that the upper cladding layer is composed of fine grains; Figure 6 The microstructure of the middle part of the cladding layer shown in (d) is composed of directional columnar dendrites, non-directional dendrites and a small part of equiaxed crystals. The main reason is that compared with the upper part of the molten pool, the undercooling degree in the middle part of the molten pool is relatively small, which creates solidification conditions for the growth of columnar dendrites and the formation of equiaxed crystals. Figure 6 Figure e is the morphology of the lower part of the cladding layer. It can be seen from the figure that there is a clear boundary between the substrate and the cladding layer. The main reason is that in the initial state of cladding, the substrate temperature is low, the cladding heat diffuses rapidly to the substrate, the temperature gradient is large, and a large degree of supercooling is formed at the boundary between the substrate and the cladding pool. Crystal nuclei are quickly formed at the boundary, resulting in the formation of planar crystals at the boundary. However, it can be seen from the figure that the planar crystals are thinner. The main reason is that as the cladding continues, the substrate temperature further increases, the temperature gradient becomes smaller, and the degree of supercooling decreases. Therefore, columnar crystals pointing to the center of the molten pool can be seen growing on the planar crystals.

[0116] In order to further analyze the composition of each part of the coating, the composition analysis of the upper, middle and lower parts of the coating was carried out respectively. The results are as follows: Figure 7 shown. Figure 7 Figures b / c / d are the SEM and RXD test results of the upper, middle and lower parts of the coating. The results show that the components of Cr, Fe, Co and Ni in the crystallization of Figure a are basically the same except that the proportion of Co atoms is slightly lower. In the middle of the coating in Figure b, the content of Cr, Co and Ni atoms all shows a downward trend, while the content of Fe atoms increases. Figure 7 Figure c in the middle is the coating transition layer, and the composition analysis of the white bright band was carried out. The results show that the content of Ni and Co in the white bright band is extremely low, and the main content is Fe and Cr. It can be considered that the white bright band generates an intermetallic compound σ phase (FeCr).

[0117] Table 4 Atomic percentage of elements at each mark

[0118]

[0119] Figure 8 The hardness of the coating obtained by different processes is compared with the hardness of the substrate. Figure 8As shown in a, the coating hardness obtained under different power parameters is only slightly lower than the substrate hardness when the power is 1.5KW, and the coating hardness obtained under other conditions is higher than the substrate hardness. The coating hardness value with the highest value of 286.6HV is the coating obtained when the power is 1.9KW. Figure 8 As shown in b, when the scanning speed is 120 mm / s, the hardness of the coating is 5% lower than the hardness of the substrate. The hardness of the coating obtained at other scanning speeds is equivalent to or even higher than the hardness of the substrate. The highest hardness occurs when the scanning speed is 100 mm / s, and the microhardness value of the coating obtained reaches 321.9 HV.

[0120] The main reason is that during the cladding process, the coating grains are effectively refined due to rapid heating and rapid cooling, and fine grain strengthening provides favorable conditions for improving the hardness of the coating; secondly, during the rapid heating and rapid cooling process, non-equilibrium compounds are easily generated in the coating, some of which provide conditions for solid solution strengthening, and some of the non-equilibrium compounds are hard phases, which further improve the hardness of the coating.

[0121] The NiCoCr alloy coating was prepared on the NiCr15Fe surface using different laser powers and scanning speeds and studied. The results show that:

[0122] 1. The coating width and dilution rate increase with the increase of laser power. When the laser power reaches 2.3KW, cracks appear in the coating. As the scanning speed increases, the coating width and dilution rate gradually decrease. When the scanning speed increases to 120mm / s, the coating is no longer continuous, forming intermittent metal melting points and pores.

[0123] 2. The coating is divided into three parts: upper, middle and lower, which are respectively the fine grain area, the mixed area of ​​equiaxed crystals and columnar crystals, and the columnar crystal area. σ phase (FeCr), i.e. white bright band, is generated between the coating and the substrate. The Cr and Co contents in the coating gradually decrease, while the Ni content is the highest in the middle part. The Fe content gradually increases in the coating, and the Fe content in the white bright band reaches a peak of 71.69%.

[0124] 3. In the experiment of changing laser power, the coating with the highest hardness value was obtained at 1.9KW, reaching 286.6HV. In the experiment of changing scanning speed, when the scanning speed was 100mm / s, the coating hardness value reached 321.9HV, while when the scanning speed was 120mm / s, the coating hardness was less than 5% of the substrate hardness.

[0125] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0126] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a high temperature anti-oxidation coating material on the surface of a NiCr15Fe alloy, characterized in that: The method comprises the following steps: NiCr1 5Fe alloy was used as the base material, CoCrNi alloy powder was used as the cladding material, the base material was pretreated, and the cladding material was clad on the base material using an ytterbium-doped fiber laser according to the set laser cladding process parameters. The set laser cladding process parameters are: laser power 1300-2100 / W, scanning speed 40-120mm / s, powder feeding speed 2r / min, and spot diameter 2 / mm.

2. The method for preparing the NiCr15Fe alloy surface high temperature anti-oxidation coating material according to claim 1, characterized in that: The laser cladding process parameters were set as follows: laser power 1900 / W, scanning speed 100mm / s, powder feeding speed 2r / min, and spot diameter 2 / mm.

3. The method for preparing the NiCr15Fe alloy surface high temperature anti-oxidation coating material according to claim 2, characterized in that: During the cladding process, the cladding material is blown out with nitrogen.

4. The method for preparing the NiCr15Fe alloy surface high temperature anti-oxidation coating material according to claim 3, characterized in that: The NiCr15Fe alloy composition, calculated by mass percentage, includes: 72.50% Ni, 14.10% Cr, 9.80% Fe, 0.30% Mn, 0.30% Ti, 0.35% Al, 0.10% C, 0.50% Si and 2.05% inevitable impurities.

5. The method for preparing the NiCr15Fe alloy surface high temperature anti-oxidation coating material according to claim 4, characterized in that: The CoCrNi alloy powder composition includes, by mass percentage, 34.54% Ni, 34.47% Co, 30.55% Cr and 0.44% inevitable impurities.

6. The method for preparing the NiCr15Fe alloy surface high temperature anti-oxidation coating material according to claim 4, characterized in that: The pretreatment of the substrate material includes sanding to remove the surface oxide layer, cleaning to remove oil with ethanol, and drying.

7. The method for preparing the NiCr15Fe alloy surface high temperature anti-oxidation coating material according to claim 6, characterized in that: The geometric dimensions of the cladding layer are: molten pool width is 480.8-1456.8 μm, total depth is 143.7-491.3 μm, molten pool depth is 69.5-373.5 μm, and layer height is 24.2-75.1 μm.

8. A high temperature oxidation resistant coating material for NiCr15Fe alloy surface, characterized in that: The coating material is prepared by the method for preparing a high-temperature anti-oxidation coating material on the surface of a NiCr15Fe alloy as described in any one of claims 1 to 7.

9. The NiCr15Fe alloy surface high temperature anti-oxidation coating material according to claim 8, characterized in that: The cross section of the coating material includes an upper layer, a middle layer, a lower layer and a transition layer at the junction with the substrate. The composition of the upper layer of the coating material includes 27.28% Cr, 31.91% Fe, 19.32% Co and 21.49% Ni in terms of atomic percentage; The composition of the middle layer of the coating material includes 26.44% Cr, 37.94% Fe, 16.11% Co and 19.51% Ni in terms of atomic percentage; The composition of the lower layer of the coating material includes 21.11% Cr, 71.69% Fe, 0.1% Co and 7.1% Ni in atomic percentage.

10. The NiCr15Fe alloy surface high temperature anti-oxidation coating material according to claim 9, characterized in that: The upper layer of the coating material is a fine-grained area, the middle layer of the coating material is a mixed area of ​​equiaxed crystals and columnar crystals, the lower layer of the coating material is a columnar crystal area, and a σ phase is generated in the transition layer at the junction of the coating material and the substrate.